Elucidating the influence of structure and Ag+ -Na+ ion-exchange on crack-resistance and ionic conductivity of Na3Al1.8Si1.65 P-1.8 O-12 glass electrolyte - Keshri, Shweta R.; Mandal, Indrajeet; Ganisetti, Sudheer; Kasimuthumaniyan, S.; Kumar, Rajesh; Gaddam, Anuraag; Shelke, Ankita; Ajithkumar, Thalasseril G.; Gosvami, Nitya Nand; Krishnan, N. M. Anoop; Allu, Amarnath R. (Acta Materialia, 2022)
Glasses are emerging as promising and efficient solid electrolytes for all-solid-state sodium-ion batteries. However, they still suffer from poor ionic conductivity and crack-resistance, which need to be improved for better battery performance, reliability, and service life. The current study shows a significant enhancement in crack resistance (from 11.3 N to 32.9 N) for Na3Al (1.8) Si-1.65 P1.8O12 glass (Ag-0 glass) upon Na+ -Ag+ ion-exchange (IE) due to compressive stresses generated in the glass surface while the ionic conductivity values (similar to 10(-5) S/cm at 473 K) were retained. In this study, magic angle spinning-nuclear magnetic resonance (MAS-NMR), molecular dynamics (MD) simulations, Vickers micro hardness, and impedance spectroscopic techniques were used to evaluate the intermediate-range structure, atomic structure, crack resistance and conductivity of the glass. MAS-NMR and MD simulations confirm the presence of Si-OAl-O-P groups in the glass, thus enabling formation of Na percolated channel regions. AC-conductivity analysis for Ag-0 and ion-exchanged Ag-0 glass suggests that the mobility of Na+ ion increases with increasing temperature. It is observed that the measured mean square displacement (root < R-2(t(p))>) for sodium cations using AC-conductivity isotherms is nearly constant up to 448 K and then increases with increasing temperature up to 523 K. From the impedance spectra for ion-exchanged Ag-0 glass, it is identified that the increase in root < R-2 (t(nu))> and thereby, the mobility of sodium-ions for Ag-0 glass is due to the structural variations in the Ag-0 glass with increasing the temperature. Overall, the mechanisms presented in this article helps in formulating better glass based electrolyte materials for room temperature or high temperature sodium-ion batteries. (C) 2022 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: amorphous; Ion-exchange; Ionic-conductivity; MD simulations; Mechanical property

Covalent organic framework cladding on peptide-amphiphile-based biomimetic catalysts - Kumar Mahato, Ashok; Pal, Sumit; Dey, Kaushik; Reja, Antara; Paul, Satyadip; Shelke, Ankita; Ajithkumar, Thalasseril G.; Das, Dibyendu; Banerjee, Rahul (Journal of the American Chemical Society, 2023)
Peptide-based biomimetic catalysts are promising materialsforefficient catalytic activity in various biochemical transformations.However, their lack of operational stability and fragile nature innon-aqueous media limit their practical applications. In this study,we have developed a cladding technique to stabilize biomimetic catalystswithin porous covalent organic framework (COF) scaffolds. This methodologyallows for the homogeneous distribution of peptide nanotubes insidethe COF (TpAzo and TpDPP) backbone, creating strong noncovalent interactionsthat prevent leaching. We synthesized two different peptide-amphiphiles,C10FFVK and C10FFVR, with lysine (K) and arginine(R) at the C-termini, respectively, which formed nanotubular morphologies.The C10FFVK peptide-amphiphile nanotubes exhibit enzyme-likebehavior and efficiently catalyze C-C bond cleavage in a buffermedium (pH 7.5). We produced nanotubular structures of TpAzo-C10FFVK and TpDPP-C10FFVK through COF claddingby using interfacial crystallization (IC). The peptide nanotubes encasedin the COF catalyze C-C bond cleavage in a buffer medium aswell as in different organic solvents (such as acetonitrile, acetone,and dichloromethane). The TpAzo-C10FFVK catalyst,being heterogeneous, is easily recoverable, enabling the reactionto be performed for multiple cycles. Additionally, the synthesis ofTpAzo-C10FFVK thin films facilitates catalysis inflow. As control, we synthesized another peptide-amphiphile, C10FFVR, which also forms tubular assemblies. By depositingTpAzo COF crystallites on C10FFVR nanotubes through IC,we produced TpAzo-C10FFVR nanotubular structuresthat expectedly did not show catalysis, suggesting the critical roleof the lysines in the TpAzo-C10FFVK.

Covalent organic framework thin-film photodetectors from solution-processable porous nanospheres - Bag, Saikat; Sasmal, Himadri Sekhar; Chaudhary, Sonu Pratap; Dey, Kaushik; Blaette, Dominic; Guntermann, Roman; Zhang, Yingying; Poloz, Miroslav; Kuc, Agnieszka; Shelke, Ankita; Vijayaraghavan, Ratheesh K.; Ajithkumar, Thalasseril G.; et al. (Journal of the American Chemical Society, 2023)
The synthesis of homogeneous covalent organic framework (COF) thin films on a desired substrate with decent crystallinity, porosity, and uniform thickness has great potential for optoelectronic applications. We have used a solution-processable sphere transmutation process to synthesize 300 +/- 20 nm uniform COF thin films on a 2 x 2 cm2 TiO2-coated fluorine-doped tin oxide (FTO) surface. This process controls the nucleation of COF crystallites and molecular morphology that helps the nanospheres to arrange periodically to form homogeneous COF thin films. We have synthesized four COF thin films (TpDPP, TpEtBt, TpTab, and TpTta) with different functional backbones. In a close agreement between the experiment and density functional theory, the TpEtBr COF film showed the lowest optical band gap (2.26 eV) and highest excited-state lifetime (8.52 ns) among all four COF films. Hence, the TpEtBr COF film can participate in efficient charge generation and separation. We constructed optoelectronic devices having a glass/FTO/TiO2/COF-film/Au architecture, which serves as a model system to study the optoelectronic charge transport properties of COF thin films under dark and illuminated conditions. Visible light with a calibrated intensity of 100 mW cm-2 was used for the excitation of COF thin films. All of the COF thin films exhibit significant photocurrent after illumination with visible light in comparison to the dark. Hence, all of the COF films behave as good photoactive substrates with minimal pinhole defects. The fabricated out-of-plane photodetector device based on the TpEtBr COF thin film exhibits high photocurrent density (2.65 +/- 0.24 mA cm-2 at 0.5 V) and hole mobility (8.15 +/- 0.64 x10-3 cm2 V-1 S-1) compared to other as synthesized films, indicating the best photoactive characteristics.

Hydroxide ion-conducting viologen-bakelite organic frameworks for flexible solid-state zinc-air battery applications - Rase, Deepak; Illathvalappil, Rajith; Singh, Himan Dev; Shekhar, Pragalbh; Leo, Liya S.; Chakraborty, Debanjan; Haldar, Sattwick; Shelke, Ankita; Ajithkumar, Thalasseril G.; Vaidhyanathan, Ramanathan (Nanoscale Horizons, 2023)
Adaptable polymer-based solid-state electrolytes can be a game-changer toward safe, lightweight flexible batteries. We present a robust Bakelite-type organic polymer covalently decked with viologen, triazine, and phenolic moieties. Its flexible structure with cationic viologen centers incorporates counter-balancing free hydroxide ions into the polymeric framework. By design, the aromatic groups and heteroatoms in the framework can be activated under an applied potential to prompt a push-pull drive, setting off the towing of hydroxide ions via weak electrostatic, van der Waals, and hydrogen-bond interactions. The frontier orbitals from a DFT-modeled structure certify this. The hydroxyl-polymer requires minimal KOH wetting to maintain a humid environment for Grotthuss-type transport. The hydroxide ion conductivity reaches a value of 1.4 x 10(-2) S cm(-1) at 80 degrees C and 95% RH, which is retained for over 15 h. We enhanced its practical utility by coating it as a thin solid-state separator-cum-electrolyte on readily available filter paper. The composite exhibits a conductivity of 4.5 x 10(-3) S cm(-1) at 80 degrees C and 95% RH. A zinc-air battery (ZAB) constructed using this polymer-coated paper as electrolyte yields a maximum power density of 115 mW cm(-2) and high specific capacitance of 435 mA h g(-1). The power density recorded for our ZAB is among the best reported for polymer electrolyte-based batteries. Subsequently, the flexible battery fabricated with IISERP-POF11_OH@FilterPaper exhibits an OCV of 1.44 V, and three batteries in series power a demo traffic signal. To underscore the efficiency of hydroxide ion transport through the complex multifunctional backbone of the polymer, we calculated the diffusion coefficient for OH- (Exp: 2.9 x 10(-5) cm(2) s(-1); Comp. 5.2 x 10(-6) cm(2) s(-1)) using electrochemical methods and MD simulations. Climbing-edge NEB calculations reveal a large energy barrier of 2.11 eV for Zn2+ to penetrate the polymer and identify hydroxide ions within the polymer, suggesting no undesirable Zn2+ crossover. Our findings assert the readily accessible C-C-linked cationic polymer's capacity as a solid-state electrolyte for ZABs and any anion-conducting membrane.

Lead-free solid state mechanochemical synthesis of Cs2NaBi1-XFeXCl6 double perovskite: reduces band gap and enhances optical properties - Udavant, Rohini; Thawarkar, Sachin; Rondiya, Sachin; Shelke, Ankita; Aher, Rahul; Ajithkumar, Thalasseril G.; Cross, Russell W.; Dzade, Nelson Y.; Jadkar, Sandesh (Inorganic Chemistry, 2023)
Efficient and stable lead-free halide double perovskites (DPs) have attracted great attention for the future generation of electronic devices. Herein, we have developed a doping approach to incorporate Fe3+ ions into the Cs2NaBiCl6 crystal unit and reveal a crystallographic and optoelectronic study of the Cs2NaBi1-xFexCl6 double perovskite. We report a simple solid-state mechanochemical method that has a solvent-free, one-step, green chemistry approach for the synthesis of Cs2NaBi1-xFexCl6 phosphor. The analysis of powder X-ray diffraction (XRD) data determines the contraction of the lattice due to the incorporation of Fe3+ cations, and this effect is well supported by X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FE-SEM), Raman spectroscopy, and solid-state nuclear magnetic resonance spectroscopy (ss-NMR). The band gap is reduced with increasing Fe content owing to the strong overlap of the Fe-3d orbitals with Cl-3p orbitals and shift of the valence band maxima (VBM) toward higher energies, as confirmed by ultraviolet photoelectron spectroscopy (UPS) and density functional theory (DFT) analyses. Photoluminescence (PL) studies of Cs2NaBi1-xFexCl6 phosphors exhibit a large Stokes shift, broadband emission, and increased PL intensity more than ten times for 15% of Fe content phosphor with enhancement in the average decay lifetimes (up to 38 ns) compared to pristine Cs2NaBiCl6 DP. These results indicate that the transition of dark self-trapping of excitons (STEs) into bright STEs enhances yellow emission. XRD, UV, and thermo-gravimetric analysis (TGA) confirmed that the Cs2NaB1-xFexCl6 DPs have good structural and thermal stabilities. Our findings indicate that the doping of Fe3+ cations into the Cs2NaBiCl6 lattice is a constructive strategy to enhance significantly the optoelectronic properties of these phosphors.

Nanosilica from Averrhoa bilimbi juice pre-treated rice husk: preparation and characterization - Dominic, C. D. Midhun; Neenu, K. V.; Begum, P. M. Sabura; Joseph, Rani; Rosa, Derval dos Santos; Duan, Yongxin; Balan, Aiswarya; Ajithkumar, T. G.; Soumya, Mary; Shelke, Ankita; Parameswaranpillai, Jyotishkumar; Badawi, Michael (Journal of Cleaner Production, 2023)
The preparation of nanosilica from rice husk without using any concentrated mineral acids is a novel concept. This work proposes a bioleaching strategy to remove metallic impurities from rice husk for the preparation of nanosilica. Herein, nanosilica (BJRHS) was prepared by calcinating Averrhoa bilimbi juice pre-treated rice husks in a muffle furnace. The chemical and atomic structures of commercial precipitated silica (CS), rice husk ash (RHA), and BJRHS were analyzed using different analytical techniques. The optimal leaching time, calcination temperature, and calcination time were 1 h, 500 degrees C, and 6 h respectively. The particle size of BJRHS was found to be 6-12 nm, which is less than that of RHA and CS. The BET surface area of BJRHS (204 m2/g) was found to be greater than RHA (110.5 m2/g) and CS (172.1 m2/g). Mesoporous nanosilica with excellent surface area and purity was produced sustainably from rice husk which could be recommended to use in the field of catalysis, polymer technology, etc.
Keywords: Averrhoa bilimbi juice; Bioleaching; Nanosilica; rice husk

Tailoring COFs: transforming nonconducting 2D layered COF into a conducting quasi-3D architecture via interlayer knitting with polypyrrole - Jain, Chitvan; Kushwaha, Rinku; Rase, Deepak; Shekhar, Pragalbh; Shelke, Ankita; Sonwani, Disha; Ajithkumar, Thalasseril G.; Vinod, Chathakudath Prabhakaran; Vaidhyanathan, Ramanathan (Journal of the American Chemical Society, 2023)
Improving the electronic conductivity and the structural robustness of covalent organic frameworks (COFs) is paramount. Here, we covalently cross-link a 2D COF with polypyrrole (Ppy) chains to form a quasi-3D COF. The 3D COF shows well-defined reflections in the SAED patterns distinctly indexed to its modeled crystal structure. This knitting of 2D COF layers with conjugated polypyrrole units improves electronic conductivity from 10(-9) to 10(-2 )S m(-1). This conductivity boost is affirmed by the presence of density of states near the Fermi level in the 3D COF, and this elevates the COF's valence band maximum by 0.52 eV with respect to the parent 2D pyrrole-functionalized COF, which agrees well with the opto-electro band gaps. The extent of HOMO elevation suggests the predominant existence of a polaron state (radical cation), giving rise to a strong EPR signal, most likely sourced from the cross-linking polypyrrole chains. A supercapacitor devised with COF20-Ppy records a high areal capacitance of 377.6 mF cm(-2), higher than that of the COF loaded with noncovalently linked polypyrrole chains. Thus, the polypyrrole acts as a ``conjugation bridge'' across the layers, lowering the band gap and providing polarons and additional conduction pathways. This marks a far-reaching approach to converting many 2D COFs into highly ordered and conducting 3D ones.
Keywords: covalent organic frameworks; Electrical conductivity

Biexciton emission in CsPbBr3 nanocrystals: polar facet matters - Titus, Timi; Vishnu, E. Krishnan; Garai, Arghyadeep; Dutta, Sumit Kumar; Sandeep, Kuttysankaran; Shelke, Ankita; Ajithkumar, Thalasseril G.; Shaji, Anil; Pradhan, Narayan; Thomas, K. George (Nano Letters, 2024)
The metal halide perovskite nanocrystals exhibit a remarkable tolerance to midgap defect states, resulting in high photoluminescence quantum yields. However, the potential of these nanocrystals for applications in display devices is hindered by the suppression of biexcitonic emission due to various Auger recombination processes. By adopting single-particle photoluminescence spectroscopy, herein, we establish that the biexcitonic quantum efficiency increases with the increase in the number of facets on cesium lead bromide perovskite nanocrystals, progressing from cube to rhombic dodecahedron to rhombicuboctahedron nanostructures. The observed enhancement is attributed mainly to an increase in their surface polarity as the number of facets increases, which reduces the Coulomb interaction of charge carriers, thereby suppressing Auger recombination. Moreover, Auger recombination rate constants obtained from the time-gated photon correlation studies exhibited a discernible decrease as the number of facets increased. These findings underscore the significance of facet engineering in fine-tuning biexciton emission in metal halide perovskite nanocrystals.
Keywords: Auger recombination; biexciton emission; Cs-133 MAS NMR spectroscopy; Perovskites; time-gatedphoton correlation

Extraction, characterization, and life cycle assessment of nanosilica from millet husk: sustainable alternative with low environmental impact - Dominic, C. D. Midhun; Rosa, Derval dos Santos; Barbosa, Rennan Felix da Silva; Anagha, O. V.; Neenu, K. V.; Begum, P. M. Sabura; Kumar, V. Aswathy; Parameswaranpillai, Jyotishkumar; Siriwong, Chomsri; Ajithkumar, T. G.; Shelke, Ankita; Pasc, Andreea (Journal of Cleaner Production, 2024)
Eco-friendly approaches for silica production are highly researched to respond increasing industrial demand for bio-nanofillers. Herein, nanosilica of 10-20 nm with mesoporosity was obtained through a mild oxalic acid pre-treatment of millet husk, followed by calcination at 700 degrees C for 2 h. Compared with commercial precipitated silica (CS) and millet husk ash (MHA) directly obtained by calcination of the husk, the pre-treated silica (MHS) had higher purity, revealed using EDX spectroscopy. Moreover, FTIR and Si-29 NMR showed a higher condensation degree in MHS with 73% of Q4 siloxane bonds vs 4% in MHA. The release of the metal and organic impurities from the husk also allows to reduce the crystallinity of MHS, and to increase the specific surface area from 82 m(2)/g in MHA to 238 m(2)/g in MHS. The type II N-2 adsorption-desorption isotherms of MHA and MHS indicate aggregates of non-porous silica particles. MHS also demonstrated remarkable thermal resilience. According to the LCA analysis, MHS has a 40% lower impact on global warming, a 38% lower impact on human carcinogenic toxicity, and a 38% lower impact on terrestrial acidification compared to rice husk nanosilica. This research thus addresses sustainability challenges by repurposing millet husks, which are readily available due to continuous millet cultivation, particularly in India. By reducing the ecological impact of husk disposal through burning, this study offers an economically viable technology for high-purity silica production, aligning with global efforts to combat climate change and promote sustainable practices.
Keywords: Life cycle assessment; Millet husk; Nanosilica; Oxalic acid

New insights into the composition and catalytic performance of VOx-Ga/γ-Al2O3 for the oxidative dehydrogenation of propane to propene - Kandasamy, Prabu; Gawali, Sheetal; Venugopalan, Aswathy Thareparambil; Manikandan, Marimuthu; Mekala, Siva Prasad; Shelke, Ankita; Ajithkumar, Thalasseril G.; Bhatte, Kushal; Raja, Thirumalaiswamy (New Journal of Chemistry, 2024)
Oxidative dehydrogenation (ODH) of propane is a promising alternative route for propene production. In this work, we developed a series of vanadium and gallium oxides supported on gamma-Al2O3 catalysts by an incipient wetness impregnation method. Among the employed catalysts, the VGA-2 showed superior catalytic activity, and the catalyst was demonstrated for longevity in ODH of propane with a stable activity using a continuous flow fixed bed reactor at 400 degrees C. H-2-TPR and UV-visible spectra showed the presence of highly dispersed monomeric VOx species with tetrahedral coordination geometry, which influences product selectivity. The characterization results also conferred that the redox nature of vanadium (V5+ and V4+) oxide and higher V5+ content on the surface of the VGA-2 catalysts are more favourable for C-H activation. In addition, the pyridine-FTIR and Ga-71 solid-state NMR studies further substantiated the presence of Lewis acid sites and tetrahedrally coordinated Ga3+Ox species that are highly responsible for the ODHP activity, respectively. Furthermore, in situ-DRIFTS studies conferred that the propane adsorption at ambient temperature showed the formation of intermediate propoxide species with the evolution of sigma-bonds and with further increase in the temperature to 325 degrees C; the stretching vibrations of the =C-H and -C-H bonds in the propylene molecule were observed. The spent catalysts were also analyzed by thermogravimetric analysis, where the optimized catalyst (VGA-2) showed the least coke deposition.

Chirality transfer from covalent organic framework nanotubes to covalent organic framework films via chirality induction crystallization - Bag, Saikat; Chatterjee, Debasmita; Mahapatra, Rohan; Sasmal, Himadri Sekhar; Khatua, Arindam; Giri, Madhurima; Paul, Satyadip; Shelke, Ankita; Almasoud, Najla; Alomar, Taghrid S.; Ajithkumar, Thalasseril G.; Sen Gupta, Sayam; et al. (Advanced Materials, 2026)
We report the synthesis of homochiral crystalline covalent organic framework (COF) films that combine rigidity and porosity, offering significant promise for heterogeneous asymmetric catalysis. We prepared enantiopure COF films from achiral diamine and trialdehyde precursors using a chiral induction crystallization strategy. A Schiff-base reaction, catalyzed by a chiral acid, namely (R)- and (S)-camphorsulfonic acids (CSA) generated a beta-ketoenamine backbone with induced chirality. (R)- and (S)-camphorsulfonic acids direct the diamine-trialdehyde condensation and induce chirality during the nucleation of COF nanotubes, enabling their periodic arrangement and the formation of homochiral thin films. We successfully synthesized six distinct COF films with three different backbone functionalities: R-, S-TpAzo; R-, S-TpDPP; and R-, S-TpBDMe2, using the two enantiomers of the chiral camphorsulfonic acids. All films displayed strong circular dichroism signals and pronounced Cotton effects, confirming their enhanced enantiopurity. Both R- and S-TpAzo films exhibited the highest crystallinity, long-range order, and permanent porosity, making them particularly well-suited for catalytic applications. To demonstrate their utility, we encapsulated a bioinspired catalyst, (Et4N)2[FeIII(Cl)bTAML], within the chiral channels of the R- and S-TpAzo films. The resulting composite created a robust heterogeneous catalytic platform for the asymmetric epoxidation of alkenes, achieving excellent activity and enantioselectivity under ambient conditions.
Keywords: chiral induction; covalent organic framework nanotube; covalent organic framework thin film; heterogeneous catalysis

Effect of sulfonation density on acid strength in ion exchange resins: Insights from solid-state NMR and density functional theory - Tumulu, Goutam Narayan; Datar, Sarvesh; Shelke, Ankita; Swain, Gitanjali; Ajithkumar, T. G.; Thirumalaiswamy, Raja; Mohan, Ojus; Mahajani, Sanjay M. (Molecular Catalysis, 2026)
Ion-exchange (IE) resins are widely used as solid acid catalysts; however, their surface acidity remains poorly characterized because their limited thermal stability precludes conventional NH3-based acidity measurements. Moreover, acid-site accessibility in IE resins is strongly governed by solvent- or reactant-induced swelling. Here, we investigate the surface acidity of commercial Amberlyst and Indion IE resins using & sup3;& sup1;P MAS NMR (Magic Angle Spinning Nuclear Magnetic Resonance), employing TMPO as a molecular probe dispersed on the resin with moderately swelling dichloromethane, thereby capturing the swollen-state acidity relevant for predicting catalytic activity. The deconvolution of the P-31 MAS NMR spectra reveals three distinct acid-strength zones arising from inhomogeneous sulfonation of the polymer matrix. The overall acidity, quantified by the area-weighted average P-31 chemical shift (delta), increases monotonically with sulfonation density. Notably, only resins containing acid sites stronger than similar to 80 ppm exhibited measurable catalytic activity in alpha-pinene isomerization, establishing a direct correlation between acidity and activity. Density functional theory (DFT) calculations on representative resin models, supported by electron-density analyses, attribute the enhancement of acid strength at higher sulfonation densities to cooperative hydrogen-bonding networks among neighboring sulfonic acid groups. Together, these findings establish P-31 MAS NMR-derived surface acidity as a catalytically relevant descriptor for the rational selection of IE resins in liquid phase acid-catalyzed chemistries.
Keywords: Acid strength; Density functional theory; heterogeneous catalysis; Ion-exchange resins; Solid acids; Solid-state NMR